PERBANDINGAN KADAR ASIATIKOSIDA DALAM EKSTRAK ETANOL 70% PEGAGAN (Centella asiatica (L)Urban) DENGAN METODE EKSTRAKSI MASERASI DAN SONIKASI SECARA LC-MS/MS - Alifia Putri Febriyanti; Siti Jazimah Iswarin; Tristy Digjayanti (Universitas Islam Negeri Alauddin Makassar, 2016)
Currently, among the many new types of modern medicine in the market there is a global tendency for going back to nature. In Indonesia, for generations plants that have medicinal properties have been used based on the ancestors experience. One of the plants oftenly used as a medicine is pennywort (Centella asiatica (L) Urban). One of the major component of pennywort is asiatikoside which has activity to accelerate wound healing. The objective of this study was to compare the extraction method that produce the highest levels of asiatikoside in 70% ethanol extract of pennywort. The extraction method were maceration and sonication in ethanol 70%. Qualitative analysis of asiatikoside was performed by thin layer chromatography (TLC) producing purplish stains after being soaked in anisaldehid sulfuric acid solution and observed under UV lamp at 366 nm. The results showed at the Rf values 0.45 in maceration and 0.43 in sonication. Quantitative analysis for assay asiatikosida using LC-MS/MS. Before quantitative analysis, validation method needs to be done. Results of the validation are: the linearity have correlation coefficient (R2) of 0.9989, LOD and LOQ at 0.06 ppm and 0.19 ppm, accuracy value (% recovery) between 98.02%-107.49%, precision value (% Coefficient of Variation) between 0.32%-3.31%, and selectivity (Retention Time) between 3.44-3.49. Asiatikoside assay results in maceration extract at 7.19% and sonication at 7.43%. The results of the validation are eligible, so that asiatikoside level were obtained by LC-MS/MS declared accurate, specific, and precise.